A Smart Picture Book Design Using Augmented Reality Technology - Suryatno Wiganepdo Soegoto; Adam Firdaus Darmawan; Aghnia Dewi Mahiranie; Fahma Maulana (Universitas Komputer Indonesia, 2022)
The developments that’s currently being experienced today are passing very fast and growing exponentially, as well as education, teaching methods from the past cannot be applied into the new era. With utilizing developing technology, teaching methods can be developed to adjust to today’s needs. The purpose of this research is to design and develop educational and entertaining picture books to motivate and interest children in learning. This research uses the prototype or designing method with the implementation of Augmented Reality technology into the picture books, where the books will show animation which will draw interest in reading and learning to children. The expected result from this research is the increase of children's literacy interest in Indonesia and implementing the use of books with Augmented Reality in Indonesian education curriculum.